2018
DOI: 10.11152/mu-1247
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between protein YKL-40 and ultrasonographic findings in active knee osteoarthritis

Abstract: The aim of our study was to analyze the level of the glycoprotein YKL-40 in patients with active knee osteoarthritis (OA) and to search possible correlations with local inflammation and ultrasound (US) findings.Material and methods: A prospective study with fifty consecutive patients with active knee OA (diagnosed based on the American College of Rheumatology criteria for OA with radiographic confirmation) was performed. Concentrations of YKL-40 in serum and synovial fluid were measured by ELISA. US examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Endstage HOA/KOA patients have increased levels of oxidative stress markers, decreased antioxidant capacity, impaired lipid metabolism, and dysglycemia 34 . Moreover, glycoprotein YKL-40, a potential marker for active inflammatory process, is involved in the pathogenesis of KOA synovitis 35 . Patients with early-and late-stage posttraumatic KOA have increased levels of circulating proinflammatory NOx and IL-6 compared with healthy controls (HCs) and KOA severity was correlated with leptin levels in both plasma (P) and SF 36 .…”
Section: Association With Clinical Scores and Changesmentioning
confidence: 99%
“…Endstage HOA/KOA patients have increased levels of oxidative stress markers, decreased antioxidant capacity, impaired lipid metabolism, and dysglycemia 34 . Moreover, glycoprotein YKL-40, a potential marker for active inflammatory process, is involved in the pathogenesis of KOA synovitis 35 . Patients with early-and late-stage posttraumatic KOA have increased levels of circulating proinflammatory NOx and IL-6 compared with healthy controls (HCs) and KOA severity was correlated with leptin levels in both plasma (P) and SF 36 .…”
Section: Association With Clinical Scores and Changesmentioning
confidence: 99%
“…12 CHI3L1 is secreted by macrophages, synoviocytes, and chondrocytes, [13][14][15][16] and can be detected at increased levels in the synovial fluid and serum of patients with inflammatory conditions, in addition to correlating with the extent of joint degradation in rheumatoid arthritis (RA) patients. 17 Inhibiting CHI3L1 has previously been shown to suppress inflammation and cortical bone degeneration in a murine osteomyelitis model system, 18 while Kim et al 19 similarly determined that knocking down this glycoprotein protected against hyperoxia-induced apoptotic death in human airway epithelial cells, whereas CHI3L1 overexpression increased the susceptibility of these cells to such apoptosis. As such, these prior data highlight CHI3L1 as an important regulator of inflammatory and oxidative stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…It can be detected in urine, blood, and synovial fluid (7). YKL-40 is a member of the 18 glycosyl hydrolase family and is widely distributed in synoviocytes and chondrocytes (8). Studies have shown that CTX-II and YKL-40 are closely related to the pathological changes of articular cartilage and can reflect the degree of inflammation of OA (9).…”
Section: Introductionmentioning
confidence: 99%